2021
DOI: 10.1002/hyp.14099
|View full text |Cite
|
Sign up to set email alerts
|

Non‐stationary control of the NAO on European rainfall and its implications for water resource management

Abstract: Water resource forecasting generally centres on understanding hydrological variability over coming months or years, so that water managers can prepare for extremes such as droughts or floods (Chang & Guo, 2020; Hao et al., 2018). Some forecasting systems seek to project further into the future to allow long-term planning of infrastructure and resilience to extremes and climate change (Svensson et al., 2015). These systems can rely directly or indirectly on outputs from Global Climate Models (GCMs; such as grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…The findings of this study also have implications for the inclusion of monthly and seasonal NAO forecasts in water management decision making, which is potentially limited due to NAO-rainfall response variability [22]. Whilst NAO forecasts may contain useful information for the north-western areas during the winter months, they are likely to be less useful in the south [21].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The findings of this study also have implications for the inclusion of monthly and seasonal NAO forecasts in water management decision making, which is potentially limited due to NAO-rainfall response variability [22]. Whilst NAO forecasts may contain useful information for the north-western areas during the winter months, they are likely to be less useful in the south [21].…”
Section: Discussionmentioning
confidence: 90%
“…For example, whilst in the north-west of the country more consistent NAO+/− wet/dry rainfall responses in winter were found, significant NAO-rainfall variability can occur in the central, southern and eastern areas, with some regions having equal likelihood of wetter/drier conditions and extremes [21]. The spatial and temporal variability in the rainfall response to the NAO across Great Britain has been noted as a potentially limiting factor in the inclusion of even highly accurate monthly/seasonal NAO forecasts in water management decision making [13,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the role of climate change in affecting the non-stationary periodicities (detected in this study) is currently unknown Yuan et al (2017). highlight the importance of suitable calibration period selection for the development of drought early warning systems, particularly in climate change scenarios.Many of these systems in Europe (e.g.Hall and Hanna, 2018;Svensson et al, 2015) rely on high-resolution hydrometeorological datasets for calibration of historical relationships, many of which are only available for recent decades(Rust et al, 2021b, Sun et al 2018. We show here that frequency statistics potentially used as calibration bases for water resource early warning systems can exhibit both multidecadal periods of stability and abrupt sub-decadal non-stationarities, driven by multiannual behaviours in the NAO.…”
mentioning
confidence: 80%
“…While stronger NAO-like multiannual periodicities have been detected in water resource variables, due to the high-band filtering function of hydrological processes (van Loon, 2013), the degree to which these behaviours are sufficiently stable to enable development of predictive utilities is currently unclear. Furthermore, existing research has shown that the sign of the relationship between NAOI and European rainfall is non-stationary at decadal timescales (Rust et al, 2021b); Vicente-Serrano and López-Moreno (2008)). This is expected to add a degree of uncertainty to the detection of lead times between multiannual periodic components in the NAO and water resource response, which is necessary in the development of early warning systems for water resource extremes.…”
Section: Introductionmentioning
confidence: 99%